Binding N_2_, N_2_H_2_, N_2_H_4_ and NH_3_ to Transition Metal Sulfur Sites: Modeling Potential Intermediates of Biological N_2_ Fixation - Sellmann, Dieter; Kisch, Horst; Hille, Andreas; Rösler, Annette; Heinemann, Frank Wilhelm; Moll, Matthias; Brehm, Georg; Reiher, Markus; Heß, Bernd Artur; Bauer, W. (Chemistry - A European Journal, 2003)
UnivIS-Import:2017-03-24:Pub.2003.forsch.sonder.sfb583.bindin

Effect of Chelate Ring Size in Iron(II) Isothiocyanato Complexes with Tetradentate Tripyridyl-alkylamine Ligands on Spin Crossover Properties - Leibold, Michael; Kisslinger, Sandra; Heinemann, Frank Wilhelm; Hampel, Frank; Ichiyanagi, Yuko; Klein, Michael; Homenya, Patrick; Renz, Franz; Toftlund, Hans; Brehm, Georg; Schneider, Siegfried; Reiher, Markus; et al. (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
Iron(II) complexes of the type [Fe(L)(NCS)(2)] with tetradentate ligands L are well known to show spin crossover properties. However, this behavior is quite sensitive in regard to small changes of the ligand system. Starting from the thoroughly investigated complex [Fe(tmpa)(NCS)(2)] [tmpa = tris(2-pyridylmethyl)amine, also abbreviated as tpa in the literature] we modified the ligand by increasing systematically the chelate ring sizes from 5 to 6 thus obtaining complexes [Fe(pmea)(NCS)(2)], [Fe(pmap)(NCS)(2)], and [Fe(tepa)(NCS)(2)] [pmea = N,N-bis[(2-pyridyl)methyl]-2-(2-pyridyl)ethylamine, pmap = N,N-bis[2-(2-pyridyl)ethyl]-(2-pyridyl)methylamine, and tepa = tris[2-(2-pyridyl)ethyl]amine]. All complexes were structurally characterized and spin crossover properties were investigated using Mo ss bauer spectroscopy, magnetic measurements, and IR/Raman analyses. The results demonstrated that only the iron complexes with tmpa and pmea showed spin crossover properties, whereas the complexes with the ligands pmap and tepa only formed high spin complexes. Furthermore, DFT calculations supported these findings demonstrating again the strong influence of ligand environment. Herein the effect of increasing the chelate ring sizes in iron(II) isothiocyanato complexes with tetradentate tripyridyl-alkylamine ligands is clearly demonstrated.
Keywords: Tetradentate pyridyl ligands; Spin crossover; LIESST effect; Mossbauer; Iron

Femtosecond transient absorption spectroscopy of silanized silicon quantum dots - Kuntermann, Volker; Cimpean, Carla Ramona; Brehm, Georg; Sauer, Guido; Kryschi, Carola; Wiggers, Hartmut (Physical Review B, 2008)
Excitonic properties of colloidal silicon quantum dots (Si qdots) with mean sizes of 4 nm were examined using stationary and time-resolved optical spectroscopy. Chemically stable silicon oxide shells were prepared by controlled surface oxidation and silanization of HF-etched Si qdots. The ultrafast relaxation dynamics of photogenerated excitons in Si qdot colloids were studied on the picosecond time scale from 0.3 ps to 2.3 ns using femtosecond-resolved transient absorption spectroscopy. The time evolution of the transient absorption spectra of the Si qdots excited with a 150 fs pump pulse at 390 nm was observed to consist of decays of various absorption transitions of photoexcited electrons in the conduction band which overlap with both the photoluminescence and the photobleaching of the valence band population density. Gaussian deconvolution of the spectroscopic data allowed for disentangling various carrier relaxation processes involving electron-phonon and phonon-phonon scatterings or arising from surface-state trapping. The initial energy and momentum relaxation of hot carriers was observed to take place via scattering by optical phonons within 0.6 ps. Exciton capturing by surface states forming shallow traps in the amorphous Si Ox shell was found to occur with a time constant of 4 ps, whereas deeper traps presumably localized in the Si-Si Ox interface gave rise to exciton trapping processes with time constants of 110 and 180 ps. Electron transfer from initially populated, higher-lying surface states to the conduction band of Si qdots (>2 nm) was observed to take place within 400 or 700 fs. © 2008 The American Physical Society.
Keywords: absorption; quantum; dots; spectroscopy

Metal thiolate complexes binding molecular nitrogen under mild conditions: [my-N_2_Ru(P^1^Pr_3_)(N_2_Me_2_S_2_) - Sellmann, Dieter; Hille, Andreas; Heinemann, Frank Wilhelm; Moll, Matthias; Rösler, Annette; Sutter, Jörg; Brehm, Georg; Reiher, Markus; Heß, Bernd Artur; Schneider, Siegfried (Inorganica Chimica Acta)
UnivIS-Import:2017-03-24:Pub.2003.forsch.sonder.sfb583.metalt